The Death of Pan: Elizabeth Barrett Browning and the Romantic Ego - Morlier, Margaret M. (Browning Institute studies, 1990)
During the past two decades Elizabeth Barrett Browning has become most appreciated for her 1856 feminist epic Aurora Leigh, a poem in which she asserted her "highest convictions upon Life and Art." Before publishing Aurora Leigh, however, she said that one of her most important poems was "The Dead Pan." When she published her two-volume collection of Poems in 1844, she insisted that "The Dead Pan" be placed last for emphasis. This poem of thirty-nine stanzas, each ending with some variation of the phrase "Pan is dead," is often overlooked today in discussions of Barrett Browning's development probably because its theme appears outdated to modern readers. Beginning with a catalogue of classical deities—such as Juno, Apollo, and Cybele—shocked by the crucifixion of Christ, the poem depicts the death of these classical gods along with their representative, Pan. In the final third of the poem they are replaced by the Christian god and his martyred son. Then the refrain "Pan is dead" changes in meaning: no longer the lament of the classical gods, the refrain becomes a joyful proclamation of the Christian poet. On a first reading, "The Dead Pan" seems simply to celebrate orthodox Christianity; it is still generally remembered as a Victorian expression of pietism or, in Douglas Bush's facetious words of 1937, a poem in which the "Greek gods are brought face to face with Christian truth and put to rout" (268).